Дослідження сіл в Інтернеті - Небі Оздемір (Народна творчість та етнографія, 2010)
In this paper, the relationship between folklore and technology, in particular internet, is studied. Village monography is still accepted as one of the main field works of folklore. Many folklorists have prepared their theses on the village monography for years. Life, therefore social sciences and folklore/cultural studies have been changed due to many factors. One of these factors is Internet. Nowadays, many outsiders who are not folklorists have created many village sites as the different types of the village monographies on Internet. There are many sites related to Turkish village on Internet. Some of them on the west villages of Turkey (the Aegean Region/Denizli-Çivril) are studied in this article. These sites, including many motifs and traditions, are like new data base for a cultural researcher/folklorist. These sites, updated periodically are virtual memory of community. As a result, these sites are the virtual monographies of the villages to be analysed closely by a folklorist.